Examining The Management and Treatment Approaches for Depression in Pregnant Women - Yakayum; Emilia, Ova; Septiana Pratiwi, Cesa (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2023)
Pregnant women suffering from undiagnosed or inadequately treated depression during their pregnancy face increased postpartum risks and jeopardize the health and safety of both mother and fetus. To understand the management of depression in pregnant women at Gamping II Community Health Centre. This qualitative research employed a case study approach. Informants were selected using heterogeneous purposive sampling, comprising 9 participants: a pregnant woman, a head of the community health centre, a doctor, two midwives, a psychologist, a psychiatric nurse, and two pharmacists. The study reveals that the depression management provided to pregnant women is not comprehensive due to the lack of post-referral care, resulting in inadequate monitoring and evaluation. There is a lack of knowledge about using mental health screening tools, understanding care for depressed mothers, and implementing guidelines for managing depression in pregnant women. These factors hinder the provision of comprehensive care. Pregnancy care for women with depression requires comprehensive health management strategies. Comprehensive care is crucial to mitigate the impact of mental health disorders experienced during pregnancy